L'ascolto del mondo - Roberto Barbanti (Kaiak)
In the face of the global crisis that we are experiencing and undergoing, the need to transform the dominant model of planetary civilization is compelling. In this paradigm transition, the sensitive dimension, although historically undervalued, has played and plays a fundamental role. It is therefore a matter of understanding the stakes of this aesthetic legacy and how it is actualized today. The dimension of feeling and listening in particular are, in fact, at the center of a dual process of a paradoxical nature, at once subjugation and emancipation. A new ecosophy of sound capable of opposing the deaf and subjugating side of listening seems to be looming as a possible line of escape from a nefarious future for humans and the world.